Angina Severity and Symptom Improvement Are Associated With Diagnostic Acetylcholine Provocation Dose in Vasospastic Angina - C. Crooijmans; Tijn P. J. Jansen; Joan G. Meeder; Valeria Paradies; Annemiek M. J. de Vos; Pier Woudstra; Tessel N. E. Vossenberg; Tim P. van de Hoef; Nicola S. Vos; Els G. M. Olde Bijvank; Stijn C. H. van den Oord; Patty Winkler; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background A coronary function test (CFT) is the recommended diagnostic test to identify coronary vasomotor dysfunction as a cause of symptoms in patients with angina and nonobstructive coronary arteries (ANOCA). Acetylcholine is the commonly used pharmacological agent for spasm provocation. We aimed to investigate an association between severity of symptoms and provocative acetylcholine dose. Methods and Results We included ANOCA patients undergoing clinically indicated CFT from the Netherlands Registry of Invasive Coronary Vasomotor Function Testing: NL‐CFT. Patients with epicardial spasm (n=251) were divided according to acetylcholine spasm triggering dose: low (2–20 mcg, EpiLOW), middle (100 mcg, EpiMIDDLE) or high (200 mcg, EpiHIGH). Patients with microvascular spasm (n=157) were analyzed irrespective of triggering dose. The patient groups were compared to each other and to a control group with negative CFT results (n=101). We assessed mean Seattle Angina Questionnaire angina frequency and summary scores at baseline and follow‐up and the proportion of patients improving or deteriorating. An inverse relationship between provocation dosage and angina frequency at baseline was found in epicardial spasm: the lower the triggering dose, the more frequently patients experienced angina (EpiLOW 48±20, EpiMIDDLE 53±21, EpiHIGH 57±19, microvascular spasm 61±21, controls 64±21, overall P=0.003). A trend was seen toward most patients improving in the high triggering dose group, and most patients deteriorating in the low triggering dose group. Conclusions A significant dose‐dependent relationship between spasm provocation and anginal complaints exists. Acetylcholine provocation dose could be incorporated as a risk stratification factor or surrogate outcome in future clinical trials. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT06083155.